Hemoadsorption improves kidney microcirculatory oxygenation and oxygen consumption, ameliorates tubular injury, and improves kidney function in a rat model of sepsis-induced AKI - Bülent Ergin; Deniz Erol Kutucu; Aysegul Kapucu; Wijnie van Dam; Lorenza Moretto; Paul Heyman; Can Ince (Scientific Reports)
Abstract Microcirculatory dysfunction, hypoxia, and inflammation are considered to be central in the pathogenesis of sepsis-induced acute kidney injury (AKI). In this experimental study, we hypothesized that extracorporeal removal of inflammatory cytokines by hemoadsorption (HA) therapy may mitigate renal injury associated with sepsis-induced AKI. To this end, we investigated renal microcirculatory oxygenation and perfusion, oxygen consumption, lactate, systemic hemodynamic variables, tubular cell integrity, inflammatory mediators, and kidney function in a rat model of septic AKI elicited by endotoxin infusion. Three groups of rats were investigated on extracorporeal circulation: HA only, LPS, and LPS + HA. Endotoxin infusion reduced cortex microcirculatory oxygenation and raised creatinine and lactate levels. Renal microcirculatory oxygenation, measured by two independent techniques (phosphorescence (µPO2) and spectrophotometry/Doppler (µHbO2sat and $$μ \text{RBCv}$$ )), was ameliorated by HA therapy. The renal oxygen consumption, lactate and creatinine levels were restored in the LPS + HA group. A reduced amount of injured tubular cells was found in histological analysis of the kidneys. This experimental study demonstrated an improvement in multiple determinants of kidney oxygenation, damage, and systemic blood perfusion by HA in a clinically relevant rat model of septic AKI. Further studies are needed to optimize and support the clinical use of HA as a renal protective strategy.